2016
DOI: 10.3349/ymj.2016.57.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Morphine Infusion Therapy in Management of Chronic Pain: Present and Future Implementation in Korea

Abstract: PurposeIntrathecal morphine pump (ITMP) infusion therapy is efficient in managing malignant and nonmalignant chronic pain refractory to standard treatment. However, the high cost of an ITMP is the greatest barrier for starting a patient on ITMP infusion therapy. Using the revised Korean reimbursement guidelines, we investigated the cost effectiveness of ITMP infusion therapy and conducted a patient survey.Materials and MethodsA retrospective chart review of 12 patients who underwent ITMP implantation was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…An interval of 334 months was required to reach cost equivalence in cancer patients with intrathecal morphine infusion therapy via an implanted morphine pump in the USA, while the interval was 24.2 months in Korea and 28 months for chronic low back pain in Canada. [10][11][12] Based on our results, IMITPP may become cost-beneficial at a shorter interval (11.44 months) than intrathecal morphine infusion therapy via an implanted morphine pump, profiting Figure 4 Interval required to achieve cost equivalence among different pre-IMITPP oral morphine equivalent dose (OMED) groups. N=19 for RD group, n=14 for HD group, and n=10 for VHD group.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…An interval of 334 months was required to reach cost equivalence in cancer patients with intrathecal morphine infusion therapy via an implanted morphine pump in the USA, while the interval was 24.2 months in Korea and 28 months for chronic low back pain in Canada. [10][11][12] Based on our results, IMITPP may become cost-beneficial at a shorter interval (11.44 months) than intrathecal morphine infusion therapy via an implanted morphine pump, profiting Figure 4 Interval required to achieve cost equivalence among different pre-IMITPP oral morphine equivalent dose (OMED) groups. N=19 for RD group, n=14 for HD group, and n=10 for VHD group.…”
Section: Discussionmentioning
confidence: 87%
“…4 In the present study, most of the drug-related adverse events were controlled by symptomatic treatments and generally subsided within a few days, which is in accordance with other studies. 11,22 It is notable that severe diarrhea was reported in two patients after conversion from systemic opioids to intrathecal morphine, which was reversed by deceleration of decreased speed of systemic opioids dosage, but not by symptomatic treatment. We considered diarrhea as a gastrointestinal withdrawal symptom associated with systemic opioids withdrawal in the two patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical setting, morphine and other opiates are generally available as acute injections, oral and buccal tablets [35,36], and intrathecal and intracerebrovascular pumps [37,38]. After a 10 mg/kg intravenous dosage of morphine, humans had an average plasma AUC 0–12 of 91.9±6.3 ng·hr/mL [36].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in eleven patients with non-cancer pain and one cancer patient that underwent IDD pump therapy in Korea indicated that the median time required to reach the financial break-even point was 24.2 months [ 12 ]. The new NHI reimbursement policy may promote wider use of IDD as a treatment option for chronic pain patients in Korea, which would affect the financial break-even point in Korean patients.…”
Section: Introductionmentioning
confidence: 99%